2015
DOI: 10.3390/ijms160920326
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Diketopyrrolopyrrole-Based Small Moleculesas Donating Materials for Organic Solar Cells

Abstract: A series of diketopyrrolopyrrole-based small molecules have been designed to explore their optical, electronic, and charge transport properties as organic solar cell (OSCs) materials. The calculation results showed that the designed molecules can lower the band gap and extend the absorption spectrum towards longer wavelengths. The designed molecules own the large longest wavelength of absorption spectra, the oscillator strength, and absorption region values. The optical, electronic, and charge transport proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…It can be concluded that the heteroatom does not change the reorganization energies. Noteworthy, that Jin and Wang obtained similar values for the reorganization energies of similar DPP compounds with side chains and additional thiophene rings: with Fu flanks 0.153 and 0.301 eV for λi and λi+, respectively, and with Th flanks 0.160 and 0.293 eV for λi and λi+, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be concluded that the heteroatom does not change the reorganization energies. Noteworthy, that Jin and Wang obtained similar values for the reorganization energies of similar DPP compounds with side chains and additional thiophene rings: with Fu flanks 0.153 and 0.301 eV for λi and λi+, respectively, and with Th flanks 0.160 and 0.293 eV for λi and λi+, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we can mention only a few theoretical works devoted to structural, electronic and CT properties of DPP with thiophene or furan flanks . As an auxiliary method, the modeling usually supports the experiment with a “standard analysis” of conjugated backbones such as ground state geometries, frontier molecular orbitals, optical and electronic band gaps, torsion potentials, and less often excited states .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reorganization energy represents the relaxation energy on the charge transfer, when going from neutral to charged states and vice versa, and consists of two terms, the inner contribution λ i determined by nuclear rearrangement alone, and the outer contribution λ o , which takes into consideration the effects of surrounding medium. Despite the fact, that the second term can be essential, it is usually excluded from a consideration, as it was done for some DPP‐thiophene derivatives . The current theoretical treatment of electronic coupling involves its calculation using one of the computational schemes to detect the conductive pathways in the crystals.…”
Section: Introductionmentioning
confidence: 99%